"A Major Quality of Life Issue": A Survey-Based Analysis of the Experiences of Adults With Laryngotracheal Stenosis with Mucus and Cough. (September 2022) - Clunie, Gemma M.; Anderson, Catherine; Savage, Matthew; Hughes, Catherine; Roe, Justin W. G.; Sandhu, Gurpreet; McGregor, Alison; Alexander, Caroline M.
Objectives: To investigate how the symptoms of mucus and cough impact adults living with laryngotracheal stenosis, and to use this information to guide future research and treatment plans. Methods: A survey was developed with the support of patient advisors and distributed to people suffering with laryngotracheal stenosis. The survey comprised 15 closed and open questions relating to mucus and cough and included the Leicester Cough Questionnaire (LCQ). Descriptive statistics, X 2 and thematic analyses were completed. Results: In total, 641 participants completed the survey, with 83.62% (n = 536) reporting problems with mucus; 79% having daily issues of varying severity that led to difficulties with cough (46.18%) and breathing (20.90%). Mucus affected voice and swallowing to a lesser degree. Respondents described a range of triggers; they identified smoky air as the worst environmental trigger. Strategies to manage mucus varied widely with drinking water (72.26%), increasing liquid intake in general (49.35%) and avoiding or reducing dairy (45.32%) the most common approaches to control symptoms. The LCQ showed a median total score of 14 (interquartile range 11-17) indicative of cough negatively affecting quality of life. Thematic analysis of free text responses identified 4 key themes—the Mucus Cycle, Social impact, Psychological impact, and Physical impact. Conclusion: This study shows the relevance of research focusing on mucus and cough and its negative impact on quality of life, among adults with laryngotracheal stenosis. It demonstrates the inconsistent advice and management strategies provided by clinicians for this issue. Further research is required to identify clearer treatment options and pathways.